스토리텔링을 활용한 이야기중심 통합지도 프로그램이 초등학생의 영어 능력과 정의적 영역에 미치는 효과 - 박서준; Park, Seo-Jun (영어교과교육, 2015)
The purpose of this paper is to develop a story-based integrated teaching program in elementary English classes and to see how it influences learners’ English ability and affective factors when applied to fourth graders of elementary school. For 19 weeks, the experimental group implemented a story-based integrated teaching program through storytelling by reconstructing existing curriculums while the control group received the general textbook-based English instruction. Storytelling activities for the experimental group were divided into cross-curricular pre-storytelling, while-storytelling, and post-storytelling activities depending on the story-based integrated teaching model. The questions from pre-English and post-English test, were used to compare the between-group improvement in English listening, reading and writing abilities. A questionnaire regarding affective factors such as interest, confidence and participation in learning English was also developed and administered as a means of comparing the two groups. The results of this study are as follows: First, the story-based integrated teaching program administered to the experimental group was more effective in improving English reading and writing skills compared to the textbook-based English instruction given to the control group. Second, the story-based integrated teaching program also had a more positive effect on the improvement in affective factors such as interest, confidence and participation in learning English as compared to the textbook-based English instruction. Based on the results, pedagogical implications were derived. KCI Citation Count: 7